The Relationship of Physical Activity with Sleep Quality in Elderly Age - Ansari; Edi Purwanto; Parellangi (Formosa Journal of Science and Technology, 2023)
National Sleep Foundation (NSF) data about 67% of 1,508 elderly people in America over the age of 65 experience sleep disturbances and as many as 7.3% of the elderly complain insomnia. Research shows that sleep quality can directly affect mental, physical and emotional health (NSF, 2017) and in a research study conducted by the University of California, that 40-50% of people aged 60 years and over experience decreased sleep quality (Ambarwati, 2018). The research design is descriptive correlation with cross-sectional approach with total sampling (48 respondents). The results showed that there was a relationship between physical activity and sleep quality for the elderly at the Orchid Elderly Posyandu, Juk Ayak Village, Telen Kutai Timur District. Elderly at Orchid Elderly Posyandu, Juk Ayak Village, Telen Kutai Timur District. There is a relationship between physical activity and quality of sleep for the elderly at the Orchid Elderly Posyandu, Juk Ayak Village, Telen Kutai Timur District.